Analisis Pengaruh Non Performing Loan dan Loan to Deposit Ratio Terhadap Profitabilitas Pada PT.Bank Syariah Mandiri Periode (2010-2014) - Putra, Rizal Rustamto; , Dr. Rini Kuswati, S.E., M.Si (2015)
The large amount of loans disbursed by a bank will determine the profitability of banks, profitability is the net result of a number of policies and decisions. Profitability ratios measure the company's ability to generate profits. Profitability is a factor that should receive attention is important because in order to establish his life, a company must be in favorable circumstances.This study aims to examine the Non Performing Loan and Loan to Deposit Ratio Profitability (Return On Assets). The research population is Bank Syariah Mandiri. The sampling method using purposive sampling with criteria established that quarterly reports from 2010 to 2014. The number of samples were analyzed using multiple linear regression analysis.Based on t test showed that the variables NPL significant and negative effect on ROA. LDR variable does not affect the ROA (profitability). Moreover Variable NPL and LDR simultaneous and significant impact on ROA. and two independent variables that affect the ROA of 81.5%. Bank Syariah Mandiri is expected to fix the problem loans and raise capital, as well as to operate effectively and efficiently. Keywords: Non Performing Loan, Loan to Deposit Ratio, Return On Assets.